Synthesis of a hydrophilic derivative of ecdysterone and development of its water-soluble form - Kozhanova, A.M.; Temirgaziyev, B.S.; Zhanarbek, A.; Tuleuov, B.I.; Seilkhanov, T.M.; Adekenov, S.M. (KU Publ., 2021)
The article presents materials on the isolation of ecdysterone substance from medicinal plant raw materials Silene wolgensis (Hornem.) Bess. ex. Spreng (Volga smolyovka). For the first time, the optimization of the method for ecdysterone substance obtaining from the aboveground part of the superconcentrator of phytoecdysteroids of the Silene wolgensis was carried out and based on it a pilot industrial regulation for the isolation of ecdysterone and an encapsulated water-soluble form were developed. It was found, that the interaction of the substrate molecule and the clathrate forms a substance that can dissolve in water and other more polar solvents, thereby solving the problem of bioavailability of the main hydrophobic drug. The method developed for producing the substance ecdysterone and its water-soluble encapsulated with β-cyclodextrin form was implemented into production at the Karaganda pharmaceutical plant. NMR studies of changes in the chemical shifts of protons of substrates and receptors illustrated that ecdysterone interacts with β-cyclodextrin to form supramolecular inclusion complexes with stoichiometric composition of 1:1.
Экдистеронның гидрофильді туындысының синтезі және оның негізінде суда еритін түрін алу
Синтез гидрофильного производного экдистерона и разработка водорастворимой формы на его основе
Keywords: ecdysterone; optimization of isolation; Silene wolgensis; β-cyclodextrin; encapsulation; water solubility; NMR; supramolecular complexes